Integrating Gamification in LMS as an Effort to Increase Kinesthetic Learner Engagement - Vitalia, Fatichananda; Miyarso, Estu (Jurnal Ilmiah WUNY, 2026)
Background: Digital education transformation demands learning systems that are adaptive to the diversity of students' learning styles. The Learning Management System (LMS) as an online learning platform has been widely used to support learning flexibility; however, it still inadequately accommodates the needs of kinesthetic learners who require physical activity and direct engagement. Objectives: This study aims to examine the potential of integrating gamification into LMS as a strategy to enhance the engagement of students with kinesthetic learning styles. Method: This study employed a literature review method, drawing on various sources and prior studies addressing LMS, gamification, and kinesthetic learning styles. Result: The review findings indicate that gamification incorporating interactive elements such as challenges, points, badges, and simulations is effective in increasing kinesthetic students' motivation and active engagement in digital learning environments. Conclusion: The integration of gamification into LMS has the potential to serve as a personalized and contextually responsive solution for kinesthetic learners, while also providing a conceptual foundation for the development of gamification-based LMS models as a more inclusive and effective digital learning innovation.